The commercial misrepresentation of environmental issues: Comparing environmental media coverage in the first world and developing nations - Raj, Sony Jalarajan; Sreekumar, Rohini (My University, 2011)
Over the past three decades the steady encroachment of business interests into the international media environments and the increasing monopolization of media ownership resulted in the escalation of commercial imperatives in media production which directly paved to a shifting representation of environmental issues. This article offers a critical appraisal of the contemporary global commercial media and its coverage of environmental issues. Influenced by the market values and the ongoing monopolization of media ownership, business interests played a key role, and resulted in a drastic change in the representation of environmental issues by the global media. Concomitant with these developments is a shift in emphasis within news and current affairs media which become distorted by the twin pressures of commercialization and market competition, giving way to an emphasis on entertainment values at the expense of reasoned and informed coverage. However, some third world media practitioners offer environmental news coverage that is informed by sustainable forms of developmentalism, while recognizing environmental issues as being both local and global phenomena. Nowadays environmental movements are purposely confined by the media as geographical and cultural identity. It miserably fails to correlate, equate, and investigate it beyond the boundaries of a nation state or personalized perspectives. This research paper analyses the practice of environmental communication by media, where news is highly influenced, and sometimes biased by policy decision, economic and financial causes, making it limited to a particular geographical and cultural realm. This essay addresses environmental communication first as a global practice transformed by commercialism, before examining more salient and creditable forms of environmental journalism utilized in developing nations that are informed by the 'glocal' nature of these issues. This research paper is based on qualitative textual analysis, interpretation and literature review on news published by the main stream media.
Keywords: eco-friendly; entertainment; global media; media commercialization; media ownership